2017
DOI: 10.1177/1357633x17748350
|View full text |Cite
|
Sign up to set email alerts
|

Keeping care connected: e-Consultation program improves access to nephrology care

Abstract: Introduction Health systems are seeking innovative solutions to improve specialty care access. Electronic consultations (eConsults) allow specialists to provide formal clinical recommendations to primary care providers (PCPs) based on patient chart review, without a face-to-face visit. Methods We implemented a nephrology eConsult pilot program within a large, academic primary care practice to facilitate timely communication between nephrologists and PCPs. We used primary care referral data to compare wait time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 32 publications
1
34
0
5
Order By: Relevance
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
See 2 more Smart Citations
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
“…More than half of the included studies were from 1 of 2 settings: 26 from the Champlain BASE program and 13 from VA settings. 7,[37][38][39][40][41][42][43][44][45][46][47][48] Of the remaining 24 studies, there were 12 from community health centers or large public health care systems, 43,[49][50][51][52][53][54][55][56][57][58][59] 8 from academic medical centers, [60][61][62][63][64][65][66][67] 2 from a nongovernmental humanitarian organization, 68, 69 1 from a not-for-profit integrated health care delivery system, 70 and 1 from a private company providing e-consult services. 71 Most studies were observational in design and lacked a control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saurman et al, 2014 [ 68 ] Telemental health emergency services → remote and regional areas VC, T New South Wales, Australia 4 S 35. Schettini et al, 2019 (first online in 2017) [ 69 ] Nephrology e-Consult program → primary care providers S&F North Carolina, USA 3 NR 36. Scott et al, 2012 [ 70 ] Specialist care advice to treat complex chronic health conditions → rural primary care providers VC Pacific Northwest, USA 4 S 37.…”
Section: Methodsmentioning
confidence: 99%
“…1 Advantages of econsults include improved patient access to specialist care, potential cost savings, 2 and convenience for both health care providers and patients. 1 The utility and feasibility of e-consults has been demonstrated across multiple specialties, including cardiology, 3,4 gastroenterology, 5 endocrinology, 6 infectious disease, 7 nephrology, 8 and dermatology. 9 Although the only data currently available addressing allergy/ immunology (A/I) e-consults come from the outpatient setting, 10 the inpatient setting is prime to incorporate asynchronous evaluations.…”
mentioning
confidence: 99%